2021
DOI: 10.3389/fphar.2021.621169
|View full text |Cite
|
Sign up to set email alerts
|

Danshen (Salvia miltiorrhiza) on the Global Market: What Are the Implications for Products’ Quality?

Abstract: Background: Danshen (Radix et rhizoma Salviae miltiorrhizae; Salvia miltiorrhiza Bunge, Lamiaceae) is commonly used in Asia, including China, Japan, and Korea with markets in America and Europe growing substantially. It is included in multiple pharmacopeias and salvianolic acid B and tanshinone IIA are used as quality markers. However, on the markets, substitutes and different processing methods often are a concern. a concern regarding patients’ safety and expected outcomes.Aims: This study aims at understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Our previous studies have found that Salvia miltiorrhiza improved the survival rate of fat transplantation and promoted the proliferation and differentiation of adipose stem cells [25][26][27]. Because Salvia miltiorrhiza is a mixed traditional Chinese medicine, different sources of production or different processing methods will affect the proportion of each component in Salvia miltiorrhiza, leading to inaccurate curative effects [11]. Therefore, identifying the key small molecules in Salvia miltiorrhiza is critical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have found that Salvia miltiorrhiza improved the survival rate of fat transplantation and promoted the proliferation and differentiation of adipose stem cells [25][26][27]. Because Salvia miltiorrhiza is a mixed traditional Chinese medicine, different sources of production or different processing methods will affect the proportion of each component in Salvia miltiorrhiza, leading to inaccurate curative effects [11]. Therefore, identifying the key small molecules in Salvia miltiorrhiza is critical.…”
Section: Discussionmentioning
confidence: 99%
“…Because Salvia miltiorrhiza is a mixed traditional Chinese medicine, different sources of production or different processing methods will affect the proportion of each component in Salvia miltiorrhiza, leading to inaccurate curative effects [11]. Salvianolic acid B (Sal-B, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Salvia miltiorrhiza Bunge, also called Danshen, is a perennial herb belonging to the family Lamiaceae and has been used to treat menstrual disorders, cardiovascular diseases, chronic pain, and thoracic obstruction over 2000 years in Asia countries [ 1 4 ]. At present, the annual consumption of medicinal materials exceeds 80,000 tons.…”
Section: Introductionmentioning
confidence: 99%
“…Salvia miltiorrhiza Bunge (SMB), a traditional Chinese medicine with the effect of promoting blood circulation and removing blood stasis, is also used as a botanical drug for the treatment of diseases in many Asian countries in addition to its widespread use in China [ 2 ]. At the same time, modern pharmacological studies have shown that SMB can inhibit thrombosis by improving blood circulation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%